Short-term chromium (VI) exposure increases phosphorus uptake by the extraradical mycelium of the arbuscular mycorrhizal fungus Rhizophagus irregularis MUCL 41833 - Gil Cardeza, Maria Lourdes (2017)
Hexavalent chromium is a potent carcinogen, while phosphorus is an essential nutrient. The role of arbuscular mycorrhizal fungi (AMF) in the uptake of P is well known and was also reported, at low levels, for Cr. However, it is unclear whether the uptake of Cr can impact the short-term uptake dynamics of P since both elements have a similar chemical structure and may thus potentially compete with each other during the uptake process. This study investigated the impact of Cr(VI) on short-term P uptake by the AMF Rhizophagus irregularis MUCL 41833 in Medicago truncatula. Bi-compartmented Petri plates were used to spatially separate a root compartment (RC) from a hyphal compartment (HC) using a whole plant in vitro culture system. The HC was supplemented with Cr(VI). Chromium(VI) as well as total Cr and P were monitored during 16 h within the HC and their concentrations determined by the end of the experiment within roots and shoots. Our results indicated that the uptake and translocation of Cr from hyphae to roots was a fast process: roots in which the extraradical mycelium (ERM) was exposed to Cr(VI) accumulated more Cr than roots of which the ERM was not exposed to Cr(VI) or was dead. Our results further confirmed that dead ERM immobilized more Cr than alive ERM. Finally our results demonstrated that the short exposure to Cr(VI) was sufficient to stimulate P uptake by the ERM and that the stimulation process began within the first 4 h of exposure.